P722 An unusual constellation of symptoms: outpatient diagnosis of neurosyphilis with no history of prior syphilis symptoms. (14th July 2019) - Liu, Elizabeth; Newbury-Palma, Eliza; Taylor, Jacob; Izokaitis, Anthony
Abstract : Background: Neurosyphilis presents in early and later stages of syphilis. Cerebrospinal fluid, meninges and vascular structures are involved in the early stages of neurosyphilis, while in the late stage; cerebral tissue and spinal cord parenchyma are affected. Neurosyphilis can manifest with many different symptoms. Diagnosis criteria remains ambiguous and treatment options are classified very low quality of evidence by World Health Organization. We present a case of neurosyphilis with progressive sensory loss whose primary and secondary phases were not detected. Methods: 52 year old male initially presented with upper respiratory symptoms, headache, facial swelling, and visual disturbances. 20 pound weight loss, positive candida throat culture, diagnosis of panuveitis, and progressive hearing loss prompted diverse differential workup. Rapid plasma reagin and fluorescent treponemal antibody absorption were positive suggesting syphilis and with neurologic symptoms met neurosyphilis diagnosis. After penicillin treatment, symptoms resolved and labs showed disease resolution. Results: RPR titer high 1:128. In 2 months, WBC count increased from 9.8 to 22.0. CSF analysis showed a neutrophilic leukocytosis with elevated protein. Repeat CSF 6 months post-treatment showed negative VDRL CSF qualitative and titer negative. RPR 1:4. Syphilis antibody ≥ 70.0 high. Conclusion: Neurosyphilis can be encountered in sensory, neuropsychiatric and neurologic domains. The incidence of syphilis in Michigan has increased from 365 to 480 cases and with a national 10.5% increase from 2016 to 2017. In this case, neurosyphilis improvement was observed with resolution of sensory deficits with penicillin treatment. Impaired cognition or mood disturbance were not observed throughout the patient's clinical course. Attention should be given to progressive sensory loss because syphilis in its early stages can be overlooked, left untreated and can lead to irreversible manifestations. This case illustrates the need for further awareness on neurosyphilis as this disease can present in forms that are not common to what the current literature shows. Disclosure: No significant relationships.